The Incomplete Medicalization of Obesity: Physician Office Visits, Diagnoses, and Treatments, 1996-2014 - Ciciurkaite, Gabriele (Public Health Rep, 2019)
OBJECTIVES: Despite increased awareness of obesity-related health risks and myriad treatment options, obesity still affects more than one-third of persons in the United States and is a substantial public health problem. Studies show that physicians play a key role in obesity prevention and treatment. The objective of this study was to examine the extent to which obesity is diagnosed and treated at the level of patient-physician interaction. METHODS: We used data from the National Ambulatory Medical Care Survey (NAMCS), a nationally representative data set of US physician office visits. We estimated the number of obesity diagnoses and prescriptions of weight-loss management solutions (exercise counseling, diet counseling, or weight-loss drugs) in clinical practice from 1996 through 2014. We also calculated rates of obesity diagnosis and compared these rates with national rates of obesity based on body mass index data from the Behavioral Risk Factor Surveillance System (BRFSS) for the same period. RESULTS: The estimated number of weight gain–related physician office visits increased from 2.3 million in 1996 to a peak of 7.6 million in 2012, and then fell to 4.5 million in 2014. National estimates of obesity diagnoses resulting from physician office visits ranged from 7.1 million in 1996 to 12.7 million in 2014 and substantially outnumbered the estimates for weight gain–related physician office visits throughout the study period. Estimates of exercise counseling and diet counseling and weight-loss medication prescriptions resulting from physician office visits fluctuated over time but never exceeded obesity diagnoses. When compared with national rates of obesity from the BRFSS, rates of obesity diagnoses resulting from physician office visits were substantially lower in the NAMCS (17%-30% vs 1%). National trends for weight-loss medication prescriptions closely mirrored those of weight gain–related physician office visits, even though fluctuations were substantial. CONCLUSIONS: Our results suggest that obesity is largely underdiagnosed and undertreated in clinical encounters. Future studies should investigate the structural changes needed to better engage physicians in obesity prevention and care. Practitioners should also reflect on their biases in treating obesity as a chronic disease.